Factors Influencing Cognitive Status in Type-2 Diabetes Mellitus Patients at Royal Prima General Hospital Medan - Arianti, Rahmi; Girsang, Ermi; Sari Mutia, Maya (Babali Nursing Research, 2024)
Introduction: Type 2 Diabetes Mellitus (DM) is a significant global health concern. In Type 2 DM, hyperglycemia results from inadequate insulin production and the body’s reduced ability to respond to insulin, a condition known as insulin resistance. Diabetes Mellitus is often associated with cognitive decline, as observed in many patients with Type 2 DM. This study aims to analyze factors influencing cognitive status in Type 2 Diabetes Mellitus patients at Royal Prima General Hospital Medan. Methods: This descriptive quantitative study used a cross-sectional design. The study population consisted of 754 patients with Type 2 DM, with a sample of 150 selected. A mini-mental state exam was used to check the cognitive status. Data were analyzed using univariate, bivariate, and multivariate methods. Results: The findings indicate that gender, education level, blood glucose status, and duration of DM significantly influenced cognitive status in Type 2 DM patients at Royal Prima General Hospital Medan, with a p-value < 0.05 for each variable. In contrast, occupational status did not show a significant influence (p-value > 0.05). Collectively, gender, education level, occupational status, blood glucose status, and DM duration impacted cognitive status in these patients (p-value < 0.05). Conclusion: Among the variables studied, the duration of Type 2 DM was the most influential factor affecting cognitive status in patients at Royal Prima General Hospital Medan.